2010
DOI: 10.1097/brs.0b013e3181d9e7a4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Central Motor Conduction Time in the Diagnosis of Compressive Thoracic Myelopathy

Abstract: Our data showed a significant pattern of CMCT parameters and low CMCT-ADM/AH ratios in patients with CTM. The measurement of CMCT is valuable as a noninvasive technique for screening patients with CTM or CCM before magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…[2][3][4]8,9 The CMCT calculated by subtracting the F-wave latencies from the latencies measured to ADM after transcranial stimulation are slightly shorter than that obtained after magnetic root stimulation. 4 This difference is due to the fact that the F-wave represents the latency to the alpha motor neuron, whereas the site of magnetic root excitation is separate to that of the spinal root exit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4]8,9 The CMCT calculated by subtracting the F-wave latencies from the latencies measured to ADM after transcranial stimulation are slightly shorter than that obtained after magnetic root stimulation. 4 This difference is due to the fact that the F-wave represents the latency to the alpha motor neuron, whereas the site of magnetic root excitation is separate to that of the spinal root exit.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies regarding the normal values of CMCT. [1][2][3][4] The conduction time for the corticospinal tract is believed to be affected by body height, since it is dependent on the length of the conduction pathway. It is unclear whether normal values of CMCT can be adapted to people of different heights, or whether aging affects the conduction time for the corticospinal tract; to our knowledge, no studies have reported age or height correlations with CMCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 They reported that the causes of deterioration were axial spread of ossification of the posterior longitudinal ligament, other spinal lesions, cerebral infarction, and peripheral neuropathy. Central motor conduction time measurements are also a useful tool for detecting functional deterioration of the motor pathway due to thoracic spinal cord compression 24 or cerebral infarction, 27,31 and the F-wave study can detect a peripheral neuropathy. 14,16,26 Consequently, our data should provide important information when a reduced JOA score following surgery is observed and those electrophysiological screenings are implemented, because our study utilized a simple clinical model of cervical myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…CMCT was determined as described previously 29,30,32 and was measured for all patients before surgery. Surface recording electrodes were placed bilaterally on the abductor digiti minimi muscle (ADM) and abductor hallucis muscle (AH) using the standard belly-tendon method.…”
Section: Electrophysiological Assessmentsmentioning
confidence: 99%